PERLINDUNGAN HUKUM TERHADAP KONSUMEN PRODUK KOSMETIK TABITA : KAJIAN TERHADAP KANDUNGAN BAHAN KOSMETIK SESUAI PERATURAN PERUNDANG-UNDANGAN.: Legal Protection For Consumers Of Tabita Cosmetics: Case Study of Cosmetic Ingridients Content in Accordance with Legislation. - Nandwani, Yurike Priya Nanekram; Abrianti, Sharda (Faculty of Law, Universitas Trisakti, 2025)
This research was conducted on three variants of Tabita cosmetic products that does not acquire distribution permits and are suspected to contain hazardous or prohibited substances. These products are commonly found on various e-commerce platforms. The issue addressed in this article is whether the contents of Tabita cosmetic products contain hazardous or prohibited substances. The research method used is normative research with a descriptive nature. The data sources used include primary, secondary, and tertiary data, which were obtained through document studies or bibliographic sources. Data analysis was conducted descriptively, with conclusions drawn deductively. Based on data obtained from the BPOM public warning page, Tabita cosmetic products are known to contain mercury and hydroquinone. Both of these chemicals have the potential to cause adverse effects on human health. According to BPOM Regulation No. 17/2022, Appendix I, hydroquinone is only allowed to be used for artificial nails with a maximum concentration of 0.02%. Meanwhile, in Appendix V of the same regulation, mercury and its compounds are prohibited for use in cosmetic products.